KETUHANAN DALAM INTEGRASI KEILMUAN - Simamora, Nur Aisah (UIN Sumatera Utara Medan, 2018)
Science has degradated in it’s form by a scientific dichotomy. a student is considered professional if only learn one discipline of certain science and not diverse knowledge. This paradigm also hit the Islamic world, where there is a dichotomy of general science and religion in the level of learning. The article wants to re-reveal and affirm the role of Islamic philosophy in life and scholarship, where Islamic philosophy since its inception has greatly appreciated the development of science. Even more than that, Islamic philosophy never developed apart from the development of science. More explicitly it can be said that Islamic philosophy barely recognizes the separation between philosophy and science. In the works of Islamic philosophy, thabi'iyyah or the sciences of physics or the empirical sciences are never separated from mâ ba'da at-thabî'ah (the sciences of metaphysics). The role of science that should create an integrative worldview with God, the attitude of life according to the favor of God, the attitude that invites the pleasure of God, the choices of life that ensure happiness in the world and in the Hereafter